Cost-effectiveness modelling of use of urea breath test for the management of Helicobacter pylori-related dyspepsia and peptic ulcer in the UK. Issue 1 (8th July 2021) - Pritchard, D. Mark; Bornschein, Jan; Beales, Ian; Beresniak, Ariel; Salhi, Hocine; Malfertheiner, Peter
Abstract : Objective: Clinical data comparing diagnostic strategies in the management of Helicobacter pylori -associated diseases are limited. Invasive and noninvasive diagnostic tests for detecting H. pylori infection are used in the clinical care of patients with dyspeptic symptoms. Modelling studies might help to identify the most cost-effective strategies. The objective of the study is to assess the cost-effectiveness of a 'test-and-treat' strategy with the urea breath test (UBT) compared with other strategies, in managing patients with H. pylori -associated dyspepsia and preventing peptic ulcer in the UK. Design: Cost-effectiveness models compared four strategies: 'test-and-treat' with either UBT or faecal antigen test (FAT), 'endoscopy-based strategy' and 'symptomatic treatment'. A probabilistic cost-effectiveness analysis was performed using a simulation model in order to identify probabilities and costs associated with relief of dyspepsia symptoms (over a 4-week time horizon) and with prevention of peptic ulcers (over a 10-year time horizon). Clinical and cost inputs to the model were derived from routine medical practice in the UK. Results: For relief of dyspepsia symptoms, 'test-and-treat' strategies with either UBT (€526/success) and FAT (€518/success) were the most cost-effective strategies compared with 'endoscopy-based strategy' (€1317/success) and 'symptomatic treatment' (€1 029/success). For the prevention of peptic ulcers, 'test-and-treat' strategies with either UBT (€208/ulcer avoided/year) or FAT (€191/ulcer avoided/year) were the most cost-effective strategies compared with 'endoscopy-based strategy' (€717/ulcer avoided/year) and 'symptomatic treatment' (€651/ulcer avoided/year) (1 EUR=0, 871487 GBP at the time of the study). Conclusion: 'Test-and-treat' strategies with either UBT or FAT are the most cost-effective medical approaches for the management of H. pylori -associated dyspepsia and the prevention of peptic ulcer in the UK. A 'test-and-treat' strategy with UBT has comparable cost-effectiveness outcomes to the current standard of care using FAT in the UK.